2015
DOI: 10.1155/2015/315174
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor Polymorphism Is Associated with Susceptibility to Inflammatory Coronary Heart Disease

Abstract: Background. Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine. This study explored the association of 173G/C polymorphism of the MIF gene with coronary heart disease (CHD). Methods. Sequencing was carried out after polymerase chain reaction with DNA specimens from 186 volunteers without CHD and 70 patients with CHD. Plasma MIF levels on admission were measured by ELISA. Patients were classified into either stable angina pectoris (SAP) or unstable angina pectoris (UAP). Genotype distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
4
22
1
Order By: Relevance
“…Previous studies have reported that the plasma MIF level of CAD group was higher than non-CAD patients and the plasma MIF level was related to the stability of the plaque [12]. Also, we demonstrated a close association between the polymorphism of MIF on the −173 position and CAD [12].…”
Section: Introductionsupporting
confidence: 77%
“…Previous studies have reported that the plasma MIF level of CAD group was higher than non-CAD patients and the plasma MIF level was related to the stability of the plaque [12]. Also, we demonstrated a close association between the polymorphism of MIF on the −173 position and CAD [12].…”
Section: Introductionsupporting
confidence: 77%
“…These findings were recently affirmed in two studies of Chinese populations [54, 55]. In a Mexican-Mestizo population, the frequency of the −794 CATT 6/7 genotype also was significantly higher in patients with acute coronary artery syndromes when compared to healthy subjects (OR=1.77) [56].…”
Section: Targeting Mif Family In Atherosclerosismentioning
confidence: 70%
“…Healthy individuals carrying the MIF-173C allele produce greater amounts of MIF protein compared with those with the MIF-GG genotype, and their serum MIF levels are significantly higher [8]. Furthermore, studies have shown that patients with severe asthma have higher serum MIF levels than those with mild asthma [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…The MIF gene maps to chromosome 22q11.2 in humans. Functional polymorphisms have been identified in the MIF promoter region: a single nucleotide polymorphism (SNP) at position –173 [guanine (G)-to-cytosine (C) transition] and a CATT 5–8 microsatellite polymorphism at position –794 [8]. Polymorphisms of the human MIF gene have been associated with increased susceptibility to or severity of a number of inflammatory and autoimmune diseases such as juvenile idiopathic and adult rheumatoid arthritis, ulcerative colitis, atopy, sarcoidosis, psoriasis and extensive forms of alopecia areata [810].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation